2015
DOI: 10.3171/2015.1.focus14767
|View full text |Cite
|
Sign up to set email alerts
|

Novel delivery methods bypassing the blood-brain and blood-tumor barriers

Abstract: Glioblastoma (GBM) is the most common primary brain tumor and carries a grave prognosis. Despite years of research investigating potentially new therapies for GBM, the median survival rate of individuals with this disease has remained fairly stagnant. Delivery of drugs to the tumor site is hampered by various barriers posed by the GBM pathological process and by the complex physiology of the blood-brain and blood–cerebrospinal fluid barriers. These anatomical and physiological barriers serve as a natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 173 publications
(139 reference statements)
0
68
0
Order By: Relevance
“…Treatments for glioma include surgical resection followed by radiotherapy and chemotherapy which is assuming an increasingly important role in the treatment [2]. However, it has severely affected the chemotherapeutic effect that blood-tumor barrier (BTB) has restricted the anti-tumor drug from entering the CNS [3]. Studies demonstrated small dose of bradykinin (BK) can selectively open BTB without affecting the permeability of normal brain tissue [4].…”
Section: Introductionmentioning
confidence: 99%
“…Treatments for glioma include surgical resection followed by radiotherapy and chemotherapy which is assuming an increasingly important role in the treatment [2]. However, it has severely affected the chemotherapeutic effect that blood-tumor barrier (BTB) has restricted the anti-tumor drug from entering the CNS [3]. Studies demonstrated small dose of bradykinin (BK) can selectively open BTB without affecting the permeability of normal brain tissue [4].…”
Section: Introductionmentioning
confidence: 99%
“…An intact BBB defends the central nervous system (CNS) from intrusion of foreign substances and maintains CNS homeostasis, including ionic and fluid balances (18). Abbott et al could show that the balance of this microenvironment is disrupted by cerebral lesions such as gliomas.…”
Section: Blood-brain Barrier (Bbb) and Cerebral Lesionsmentioning
confidence: 99%
“…Malignant brain tumors, including GBM, alter the normal BBB by secreting humoral factors such as bradykinin, histamine, serotonin, and platelet-activating factor,14 thereby deregulating vascular permeability, producing hypoxia-induced changes, and modifying carrier-mediated efflux 13. The alterations in vascular permeability are related to diffuse upregulation and redistribution of aquaporin 4 on astrocyte membranes, decreased claudin and occludin expression within the tight junction complex, basal membrane disruption, and leaky neovascularization 13.…”
Section: The Blood–brain Barrier (Bbb)mentioning
confidence: 99%